Sistem Pendukung Keputusan Pemilihan Distributor Terbaik Dengan Metode SAW - Helmi Prilani; Besus Maula Sulthon (STMIK Budi Darma, 2022)
In the assessment of the selection of the best distributor at PT. Borden Eagle Indonesia there are several determining factors in the assessment. The assessment is still not optimal because it uses manual calculations and seems subjective. Because of this problem, the design of the right system can provide solutions to help and facilitate the decision making of the selection of the best distributor in accordance with the criteria that have been determined by the company. The Decision Support System using the Simple Additive Weighting (SAW) method is very suitable in the selection of the best distributor with an assessment where there are several criteria, each of which has an assessment weight so as to provide a more effective and accurate assessment of the selection of the best distributor. The criteria used to measure the assessment are 5 (five) namely Sales Growth, General Management and Compliance, Sales Tools, Inventory Management and Financial. The final result of the calculation with the SAW method shows that the alternative A4 is on behalf of the distributor PT. Anugerah Keluarga Jaya east Surabaya region and alternative A10 on behalf of distributor PT. Wono Perkasa Mandiri Tulung Agung region is ranked in the top 2 winners of the best distributors